2017
DOI: 10.1136/lupus-2017-000240
|View full text |Cite
|
Sign up to set email alerts
|

Repository corticotropin injection in patients with persistently active SLE requiring corticosteroids: post hoc analysis of results from a two-part, 52-week pilot study

Abstract: ObjectivePost hoc analyses evaluated the effectiveness and safety of repository corticotropin injection (RCI) in patients with persistently active SLE over 52 weeks.MethodsPatients were initially randomised to 40 U daily or 80 U every other day RCI (n=26) or placebo (n=12) for the 8-week double-blind period. Completers entered the open-label extension (OLE; n=33) receiving 16, 40 or 80 U RCI 1–3 times/week and were followed through week 52. Outcomes included proportion of responders based on a novel index (res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…The effectiveness of RCI for the treatment of SLE has been demonstrated in previous clinical studies [ 10 12 ]. Findings from a pilot study [ 11 ] and subsequent post hoc analyses [ 12 ] suggested that RCI is safe and may be effective for treating patients who have persistently active SLE despite treatment with moderate-dose glucocorticoids. These results provided the impetus for further evaluation of RCI in a larger study of SLE.…”
Section: Introductionmentioning
confidence: 97%
“…The effectiveness of RCI for the treatment of SLE has been demonstrated in previous clinical studies [ 10 12 ]. Findings from a pilot study [ 11 ] and subsequent post hoc analyses [ 12 ] suggested that RCI is safe and may be effective for treating patients who have persistently active SLE despite treatment with moderate-dose glucocorticoids. These results provided the impetus for further evaluation of RCI in a larger study of SLE.…”
Section: Introductionmentioning
confidence: 97%
“…16 While this exploratory study found that numerical differences were not statistically significant in the primary endpoint, a composite responder index, secondary endpoints and post hoc analyses linked RCI treatment to sustained improvements in SLE signs and symptoms and a tolerable safety profile. 16,17 These results supported the design of a wellpowered, ongoing, randomized, double-blind placebocontrolled study (NCT02953821) to evaluate 24 weeks of treatment with RCI in patients with persistently active SLE despite treatment with moderate-dose corticosteroids.…”
Section: Safetymentioning
confidence: 67%
“…12 RCI has been used successfully to treat patients with SLE exacerbations not controlled by conventional treatments. [13][14][15][16][17] In the United States, DM has a prevalence of 1 to 6 per 100,000 persons, and PM ranges from the largest fraction with approximately 10 per 100,000 persons in the United States down to the rarest condition that should only be diagnosed by exclusion. 18 Glucocorticoids are used for first-line treatment of patients with DM/PM, followed by (or in conjunction with) immunosuppressive maintenance; in case of intolerance or insufficient response, oral cyclosporine or intravenous immunoglobulin G may be used and, upon relapse or interstitial lung disease, rituximab or cyclophosphamide may be considered.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate post hoc analysis of these pilot study data, treatment with RCI demonstrated sustained improvements in disease activity over the 52-week study period. 23 These results provide a rationale for further clinical investigation of RCI for the treatment of persistently active SLE in larger studies evaluating validated response measures, such as the SRI-4. Here, we describe the design and baseline patient characteristics of this multicentre, randomised, double-blind, placebocontrolled trial.…”
mentioning
confidence: 75%